Reframing resilience: Dynamic capabilities and the evolving role of international financial institutions - Anthony Bartzokas; Tania Gómez Carrión (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2025)
This paper examines how International Financial Institutions (IFIs) can adapt to an era defined by geopolitical fragmentation and the erosion of multilateralism by harnessing their dynamic capabilities-specifically, their capacities to sense, seize, and transform in response to systemic shifts. Drawing on a Dynamic Capabilities Framework (DCF), we conceptualize IFIs resilience as a global public good, fundamental to sustaining development finance amid evolving global challenges. We propose a novel taxonomy that links the core elements of IFI business models to their institutional micro-foundations, and we identify two key mechanisms for amplifying impact: (i) the co-design of blended finance initiatives with the private sector, and (ii) the diffusion of institutional capabilities to Development Finance Institutions (DFIs) in the Global South. Our analysis positions IFIs as agents of systemic learning and knowledge transfer, underscoring the pivotal role of endogenous institutional reform in fostering resilient, sovereign financial architectures aligned with the Sustainable Development Goals.
Keywords: F35; G23; O16; H81; O19; 330; International Financial Institutions; Dynamic Capabilities Framework; Blended Finance; Institutional Diffusion; Local Currency Financing